2021
DOI: 10.1021/acs.langmuir.1c00178
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Maximum in the Adsorption of Aqueous Surfactant Mixtures: Neutron Reflectometry of Mixtures of Zwitterionic and Ionic Surfactants at the Silica–Aqueous Interface

Abstract: The adsorption of two zwitterionic surfactants, dodecyldimethylammonium propanesulfonate (C12PS) and dodecyldimethylammonium carboxybetaine (C12CB), and of their mixtures with the cationic dodecyltrimethylammonium bromide (C12TAB) and the anionic sodium dodecylsulfate (SDS) at the silica–water interface has been studied by neutron reflection (NR). The total adsorption, the composition of the adsorbed layer, and some structural information have been obtained over a range of concentrations from below the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…While a significant amount of work has been carried out to examine surfactant adsorption onto various surfaces, little is known regarding the surface adsorption behavior of the mixed IL/surfactant systems discussed above. In this study, we aim to provide a more detailed analysis of the adsorption behavior and adsorbed layer structure of both the IL/T-20 system as well as the more commonly used IL/TX-100 system on GO surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…While a significant amount of work has been carried out to examine surfactant adsorption onto various surfaces, little is known regarding the surface adsorption behavior of the mixed IL/surfactant systems discussed above. In this study, we aim to provide a more detailed analysis of the adsorption behavior and adsorbed layer structure of both the IL/T-20 system as well as the more commonly used IL/TX-100 system on GO surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have developed a series of zwitterionic molecules as the surfactants to form the high surface-active mixtures, mainly focused on their ability to reduce IFT, emulsifying characteristics for oil–water systems with the relatively low viscosity. ,, Herein, we constructed a mixed synergistic emulsion system by introducing the zwitterionic cocoamidopropyl sulfonate betaine (CSB) and anionic sodium dodecyl benzene sulfonate (SDBS). The performance of the mixed systems on heavy oil emulsions was studied in terms of surface tension, IFT, droplet size distribution, apparent viscosity, emulsion stability, viscosity reduction, and viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Since betaine is a zwitterionic surfactant, its positive charge in the molecule is electrostatically attracted to the negative charge of the anionic surfactant, which increases surface excess and potentially improves film stability of the foam . However, high adsorption occurred for betaine because of the electrostatic attraction between the positively charged quaternary ammonium groups in betaine and the negatively charged sandstone, which is about 10 times higher than that of an anionic surfactant on sandstone. , By blending anionic surfactants with betaine surfactants, anionic surfactant adsorption is expected to be influenced. Mannhardt et al have observed that the adsorption of the anionic/betaine blend is comparable to that of betaine surfactant itself.…”
Section: Introductionmentioning
confidence: 99%
“…Mannhardt et al 13 have observed that the adsorption of the anionic/betaine blend is comparable to that of betaine surfactant itself. Ma et al 15 have observed that although anionic sodium dodecyl sulfate (SDS) does not normally adsorb at the silica−water interface, SDS adsorbs strongly and cooperatively with betaine surfactants (dodecyldimethylammonium propanesulfonate) at a fractional of SDS up to about 0.5.…”
Section: Introductionmentioning
confidence: 99%